(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Pain after thoracic surgery can lead to immobility, ineffective breathing and stasis of secretions, resulting in lung collapse, pneumonia and thrombosis. Therefore, postoperative pain relief is very important to bring comfort to the patient, reducing pulmonary and cardiovascular complications after surgery. Objectives: Evaluation of the ultrasound-guided continuous erector spinae plane block for postoperative analgesia after thoracic surgery and investigation of hemodynamic, respiratory, complications and side - effects of erector spinae plane block. Research objects and methods: Descriptive, cross - sectional study. 100 patients at Da Nang Oncology Hospital, ASA I-III under thoracic surgery. Participants received a 30 ml bolus of Levobupivacaine 0.25% followed by infusion of levobupivacaine 0.125% (10-15 ml/h) for 48 hours. Results: Static VAS scores at 1 hour 1.75 ± 0.61; after 24 hours was 1.53 ± 0.55; after 48 hours was 1.37 ± 0.53. Dynamic VAS scores at 1 hour after surgery was 3.56 ± 0.89; after 24 hours was 2.00 ± 0.71; after 48 hours was 1.96 ± 0.67. Quality of recovery after 24 hours was 129 points (101-146.5 points) and after 48 hours was 138 points (117-149 points) are both greater than 121 points (good quality of recovery). 1 case (1%) of vascular impingement (1%), 4 cases (4%) of nausea or vomiting. Conclusion: Efficacy, safety, high success rate, low risk of side-effects, complications and good quality of recovery after thoracic surgery.